Analysis of Child Poverty Using a Multidimensional Approach in Indonesia - Mahlil Andre Putra; Fery Andrianus; Melinda Noer (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Poverty prevents children from being able to fulfill their basic rights such as their need to learn, access to basic services, obtain a better education and participate in society. This research was conducted to examine the multidimensional child poverty. The results showed that the percentage of children living in multidimensional poverty was 35,54 percent. In the age group of 0-6 years, the dimension that was most deprived was health, while in the age group of 7-17 years, the dimension that was most deprived was food. On average, 32,9 percent of children aged 0-6 years are deprived in two or more dimensions, and 33.9 percent of children aged 7-17 years are deprived in two or more dimensions of basic needs. This study used logistic regression as a research method to identified the probability of child being poor. The result showed that the number of children, occupation of the household head, region, education of the household head and gender of the household head were significant variables affecting children's likelihood of being poor, as well as the interaction variables between the number of children*occupation of household head, the number of children*region and the number of children*education of household head. However, the gender of the kids variables did not have a significant effect.